A profile of academic stress in the full-day school system: a case study of junior high school students - Hasnaini Hasnaini; Abdul Saman; Aswar Aswar; Maslina Maslina (JPGI (Jurnal Penelitian Guru Indonesia), 2026)
This study aims to explore the nature of academic stress among students in a full-day school system. The study employs a qualitative approach using a case study design focused on a middle school student selected through purposive sampling based on indications of academic stress, such as difficulty concentrating, fatigue, and decreased motivation to learn. Data collection was conducted through observation, semi-structured in-depth interviews, and documentation. Data were analyzed using inductive thematic analysis, while data validity was strengthened through triangulation of sources and techniques. The results indicate that academic stress is characterized by physical and mental fatigue, anxiety, decreased motivation to learn, and maladaptive behaviors during learning. The findings suggest that a packed academic schedule, high academic demands, and limited rest time are associated with the emergence of academic stress in students. This study underscores the importance of self-management-based guidance and counseling support to help students adapt more effectively.